(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article provides information on the most effective tools aimed at the development of cerebral palsy children’s motor skills, and cerebral palsy is widely covered about the importance of curative physical education in increasing children’s movement activity.